Inovasi Material Beton Berbasis Limbah : Studi Pengaruh terhadap Kuat Tekan - Diah Sarasanty; Tri Asmorowati, Erna (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
One of the impacts of the growth of activities in the transportation sector is the disposal of rubber tire waste. The increasing number of motorized vehicles in society has caused an increase in tire waste. Especially in developing countries, the use of plastic bottles has become an inevitable and unavoidable necessity for society. Inadequate waste management and handling causes negative impacts on the environment, such as hazards to human health, to animal life, soil, water, and air pollution. The purpose of this study was to reduce environmental pollution by testing the compressive strength of concrete made with a mixture of waste. Experiments were conducted in the laboratory with concrete cylinder test objects with a diameter of 150 mm and a height of 300 mm. The proportion of waste mixture, Polyethylene Terephthalate (PET), Rubber Powder, Waste Metalized Film Food Packaging (WMFFP) to fine aggregate was 0%, 5%, and 10%, each variation. The test results showed a compressive strength of 17.62 MPa, 15.29 MPa, and 14.83 MPa at the percentage of waste mixture. From this data, it can be concluded that waste materials can be used as a substitute for sand in concrete.